Computer Vision-Based Library Management System. Issue 2 (2nd April 2016) - Xi, Qingkui; Zhang, Qian; Hu, Wenliang; Xin, Wen
ABSTRACT: The article presents a library management system composed of several surveillance cameras and a personal computer (PC). The system can secure a computer room against theft and detect fire in a stack room. Based on computer vision and database technology, this article proposes a library management system comprising several surveillance cameras, a PC, and software (written in C++). The system can continually capture and analyze images to determine whether people are present in the images. The system stores the analysis results in a database. These results are used for various applications. Computer vision technology can be used for safeguarding a library. There are many surveillance cameras in most university libraries, and the C++ language is popular. Thus, the system can be adopted in libraries for providing a safe environment. In technology, the system cannot be used to spy on what library materials library users are reading. This system helps librarians and increases the level of automated library management. Computer vision technology is applied to library management.